A dimensão estética na formação do educador: a construção de um ideário coletivo. - Marques, Edite Colares Oliveira (2008)
The aim of this paper is to think over the aesthetics dimension in the training of our teachers from the Undergraduate Course and the Education Course, because we believe it is essential for the teacher to offer a meaningful teaching to his students, plenty of rich cultural experiences. Such training should make him worry about the creative processes that involve the children and the adolescents in the education period. In order to approach this subject, we divided the thesis in ten chapters. After introducing the subject matter, we made a compilation of the historical moments, since the Renaissance, when the aesthetics is appreciated in its human formation dimension, to forward in the third and fourth chapters, to deal with the teachers training and the teaching of arts from the beginning of the history up to the modern age. From the fifth chapter on, we focused on the brazilian reality, clarifying relevant aspects of our sociocultural features up to the present days, aiming to prepare the reader to our main focus, the teaching of arts in Brazil nowadays. In the eight chapter, we think over the aesthetics field in the teachers training area. Thus, we concluded that, although the guidelines to the teachers training require a knowledge by the teachers, in terms of culture, arts and aesthetics, these elements are absent in the Undergraduate and Pedagogy programs. Yet, in connection to the teachers training, it is assumed in this paper that even the teachers of arts need, in their teaching, specific knowledge in their area. The great majority of teachers, in spite of teaching arts, they are graduated in other areas; it can be explained by the lack of Undergraduate courses offerred in this area. According to the situation mentioned above, this thesis proposes, in its methodology, an action research by which were done pragmatic actions aiming a training process to a group of teachers in which the art was seen as a central axis, with the purpose of being an option to the interested in adding experiences with arts and so that, it improves the creative process of scholar teaching. The tools used were: the creation of a professional association linked to the teaching of arts; maintenance of a group of study in arts, culture and education; achievement of seminars and workshops; installation of an audio visual room, as well as the creation of a study room connected to the research. We end this present paper exhibiting what is a consensus among the authors: the imperative quality of the art training in the human development, for several aspects: the stimulus to the imagination, the mastery of techniques, the maleability of the thought, so on. We believe that the process of the syllabus reformulation of the Pedagogy and Undergraduate Courses in general, due to the new teachers training guidelines, offers a great opportunity of training in its totality, as we can see, that allows a more consistent cultural politics to the teachers training.